Internalization of Multicultural Education in Public Senior High Schools of Gunungsitoli City - Annisa Caniago; Azizah Hanum OK; Yusnaili Budianti (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study explores the internalization of multicultural education values in two high schools in Gunungsitoli City, namely SMA Negeri 1 and SMA Negeri 3. Using a qualitative phenomenological approach, the research seeks to understand the lived experiences of principals, teachers, and students in applying multicultural values within the school environment. Data were collected through observations, unstructured interviews, and documentation, and analyzed using Miles and Huberman’s interactive model with triangulation for data validity. The findings reveal that the internalization process occurs through habituation, curriculum integration, role modeling by teachers, extracurricular activities, and the establishment of inclusive school culture. The impact is evident in students’ improved tolerance, empathy, and ability to manage conflicts peacefully. Nevertheless, challenges such as stereotypes, limited contextual teaching materials, inconsistent teacher training, and symbolic implementation remain obstacles. This study contributes theoretically to the discourse on multicultural education and provides practical recommendations for schools and policymakers to strengthen inclusive educational spaces that reflect Indonesia’s diversity.